ANALISIS APLIKASI PENGGUNAAN PUPUK KNO3 PADA BUDIDAYA KEDELAI - Wijayanto, Budi (Jurnal Ilmu-Ilmu Pertanian, 2019)
One of the commodities that needs to be considered in Galur Subdistrict, KulonProgo Regency, DIY is soybean, because it experiences a productivity reduction. Soybean productivity decline is a reality of the inability of farmers to produce soybeans with existing planting areas. One of the technologies to overcome the national demand deficit for domestic soybean yields is fertilization with KNO3 fertilizer. This research was carried out at five FFS locations in May - August 2018 and the variety used was Grobogan variety. KNO3 fertilizer is applied by spraying it as a leaf fertilizer. The analysis showed that the KNO3 fertilization treatment showed more varied and higher productivity results compared to controls. The results of KNO3 fertilization also show varied results for different locations. From a financial point of view, the KNO3 fertilization treatment shows more favourable results than those without treatment.